Stigma and other correlates of sharing injection equipment among people with HIV in St. Petersburg, Russia - Simeon D. Kimmel; Jeffrey H. Samet; Debbie M. Cheng; Marina Vetrova; Bulat Idrisov; Sarah L. Rossi; Lindsey Rateau; Kristina Astone; Amy Michals; Emily Sisson; Elena Blokhina; Natasha Milet-Carty; et al. (Taylor & Francis Group, 2024)
ABSTRACTStigma that people with HIV who inject drugs experience negatively impacts HIV and substance use care, but stigma's association with sharing injection equipment is not known. This is a cross-sectional analysis of data from two studies of people with HIV reporting drug injection (N = 319) in St. Petersburg, Russia (September 2018-December 2020). We used logistic regression to examine associations between HIV stigma and substance use stigma scores (categorised into quartiles) and past 30-day equipment sharing, adjusting for demographic and clinical characteristics. Secondary analyses examined associations of arrest history and social support with sharing equipment. Almost half (48.6%) of participants reported sharing injection equipment. Among groups who did and did not share, mean HIV stigma (2.3 vs 2.2) and substance use stigma (32 vs 31) scores were similar. Adjusted analyses detected no significant associations between HIV stigma quartiles (global p-value = 0.85) or substance use stigma quartiles (global p-value = 0.51) and sharing equipment. Neither arrest history nor social support were significantly associated with sharing equipment. In this cohort, sharing injection equipment was common and did not vary based on stigma, arrest history, or social support. To reduce equipment sharing, investments in sterile injection equipment access in Russia should be prioritised over interventions to address stigma.